Properties Of Multi-Walled Carbon Nanotubes-Woven Kenaf-Woven Glass Reinforced Epoxy Laminated Composites - Mohamad, Mohd Hafizi (Universiti Sains Malaysia, 2017)
The fiber reinforcement epoxy laminated composites have been widely used in many applications. The aim of this study is to investigate the effect of multi-welled carbon nanotubes (MWCNT) addition in woven kenaf epoxy laminated composites. Woven kenaf/epoxy composites with and without MWCNT were fabricated using vacuum bagging. 1 vol % MWCNT was added into woven kenaf/epoxy laminated composite using spraying and solution method. Flexural test was employed to evaluate the flexural properties of the composite samples. The results were supported by morphological observation. The morphological observation of the composites fracture surface revealed that delamination failure occurred in MWCNT/woven kenaf/epoxy laminated composite prepared by spraying method. Regardless number of ply in the composites laminates both spraying and solution method decrease the flexural strength and flexural modulus of MWCNT/woven kenaf/epoxy composites. Density results show that addition of MWCNT in composites laminate reducing the weight of woven kenaf/epoxy laminated composites. Further investigation on hybrid composites showed that MWCNT/woven glass/woven kenaf/epoxy laminated hybrid composites exhibited 44% flexural strength and modulus increase compared to MWCNT/woven kenaf/epoxy laminated composites respectively